Agrotechnical and Operational-Technological Indicators of Disk Harrows - S.Zh, Bekzhanov; M.K, Bisenov; A.E, Zhusypbekova (Research Parks Publishing LLC, 2025)
One of the key elements of grain crop cultivation technology is soil cultivation, which accounts for up to 30% of the total costs of growing agricultural crops. Therefore, the development of new and improvement of existing tillage tools is a highly pressing issue. The tillage system should be aimed at creating the soil structure so that the conditions for the growth and development of crops are most favorable in each zone. Disc harrows are the most widely used tools for surface and shallow tillage, loosening the topsoil, leveling the field surface, breaking up the soil crust, crumbling clods of soil, and destroying weeds, as well as the application of seeds and fertilizers in accordance with agrotechnical requirements. This article examines the agrotechnical, operational and technological performance of the BDM-4x4R disc harrow and the classic BDT-3 disc harrow when plowing rice crop rotation fields.